Õpetaja mälestuseks - Sedakova, Irina; Valentsova, Marina (Mäetagused, 2023)
The renowned philologist Nikita Tolstoi promoted revolutionary ideas not only in Russian but also in the worldwide Slavonic studies. He, together with Svetlana Tolstaia, established the Moscow school of ethnolinguistics, the methodology of which is becoming increasingly topical, covering novel themes, and the number of researchers working in this field in different countries grows year by year. The 100th birth anniversary of the academician instigated his disciples to review their mentor’s work in order to evaluate his scientific contribution from the perspective of modernity and to analyse the evolution of his ideas.